Spaceflight Induced Disorders: Potential Nutritional Countermeasures - Costa, Fabio; Ambesi-Impiombato, Francesco Saverio; Beccari, Tommaso; Conte, Carmela; Cataldi, Samuela; Curcio, Francesco; Albi, Elisabetta (Frontiers in Bioengineering and Biotechnology, 2021)
Space travel is an extreme experience even for the astronaut who has received extensive basic training in various fields, from aeronautics to engineering, from medicine to physics and biology. Microgravity puts a strain on members of space crews, both physically and mentally: short-term or long-term travel in orbit the International Space Station may have serious repercussions on the human body, which may undergo physiological changes affecting almost all organs and systems, particularly at the muscular, cardiovascular and bone compartments. This review aims to highlight recent studies describing damages of the molecular mechanisms underlying the disorders of the human body induced by the space environment for microgravity, and radiation. All novel conditions, to ally unknown to the Darwinian selection strategies on Earth, to which we should add the psychological stress that astronauts suffer due to the inevitable forced cohabitation in claustrophobic environments, the deprivation from their affections and the need to adapt to a new lifestyle with molecular changes due to the confinement. In this context, significant nutritional deficiencies with consequent molecular mechanism changes in the cells that induce to the onset of physiological and cognitive impairment have been considered.